Upaya Menurunkan Kekambuhan Pada Klien Halusinasi Menggunakan Antipsikotik - Ruswanti, Ruswanti, ARUM PRATIWI, SKp., M.Kes (2017)
Background:prevalence of clients experience hallucinations in the most common in individual with schizophrenia. hallucinations are a loss of the ability of individuals to disguise stimulation of the mind (internal) and stimuli from the outside world (external) where the client or perception clients give an opinion without any real stimulus. Objective: the aim of this study is apply nursing care about giving antipsychotic programme as one of strategies to reduce the recurrence of hallucinations. Methods: The authors method of this study is case study using descriptive approach to take care vof the patient with hallucinations. Result:The result of this study of the patients with impaired sensory perception of visual hallucinations can reduce the intensity of recurrence after administration of antipsychotic drugs. Conclusion: The nursing problem is resolved in part, required the cooperation between client, family, and health care workers for the success of the nursing process.